A Comprehensive Review of Skull Base Osteomyelitis: Diagnostic and Therapeutic Challenges among Various Presentations - Khan, Muhammad Adnan (Asian J Neurosurg, 2018)
Skull base osteomyelitis (SBO) is a complex and fatal clinical entity that is often misdiagnosed for malignancy. SBO is commonly a direct complication of otogenic, sinogenic, odontogenic, and rhinogenic infections and can present as central, atypical, or pediatric clival SBO. This review describes the clinical profile, investigational approach, and management techniques for these variants. A comprehensive literature review was performed in PubMed, MEDLINE, Research Gate, EMBASE, Wiley Online Library, and various Neurosurgical and Neurology journals with the keywords including: SBO, central or atypical SBO, fungal osteomyelitis, malignant otitis externa, temporal bone osteomyelitis, and clival osteomyelitis. Each manuscript's reference list was reviewed for potentially relevant articles. The search yielded a total of 153 articles. It was found that with early and aggressive culture guided long-term intravenous broad-spectrum antibiotic therapy decreases post-infection complications. In cases of widespread soft tissue involvement, an early aggressive surgical removal of infectious sequestra with preferentially Hyperbaric Oxygen (HBO) therapy is associated with better prognosis of disease, less neurologic sequelae and mortality rate. Complete resolution of the SBO cases may take several months. Since early treatment can improve mortality rates, it is paramount that the reporting radiologists and treating clinicians are aware of the cardinal diagnostic signs to improve clinical outcomes of the disease. It will decrease delayed diagnosis and under treatment of the condition. However, due to rarity of the condition, complete prognostic factors have not fully been analyzed and discussed in the literature.